AL-WASATHIYYAH UNTUK GEN-Z: PERSPEKTIF HABIB HUSEIN JA'FAR AL-HADAR - Annisa Annisa (TASHWIR, 2023)
Abstract: The concept of al-wasathiyyah has now become the direction or school of Islamic thought for the benefit of the Islamic world at this time. This shows that Muslims should take the middle way, not to be extreme and not to be fanatic in religion. This research uses qualitative methods with library research. Data was collected using exploratory methods, interpretation, and analysis. After the data is collected, it is then analyzed using a descriptive content analysis technique. The results of the research found are Habib Husein Ja'far al Hadar's thoughts in conveying wasathiyyah is very necessary considering the many threats of radicalism, racism and fanaticism, especially the Z-gen which is easily provoked. In the social, cultural and religious context, it is important for Gen-Z to understand and respect existing diversity, uphold the values of moderation in religion, and work together in creating a harmonious and tolerant environment. From Habib Ja'far's delivery, it was very easy for various groups to accept. The media that he often uses in preaching is social media.Keywords: Al-Wasathiyyah, Habib Ja’far, Gen-Z. Abstrak: Konsep al-wasathiyyah saat ini telah menjadi arah atau aliran pemikiran Islam untuk kepentingan dunia Islam pada saat ini. Hal ini menunjukkan bahwa hendaknya umat Islam mengambil jalan tengah, tidak ekstrim dan tidak juga selayaknya bersikap fanatik dalam beragama. Penelitian ini menggunakan metode kualitatif dengan studi pustaka (library research). Data dikumpulkan menggunakan metode eksploratif, interpretasi, dan analisis. Setelah data terkumpul, lalu dilakukan analisis menggunakan teknik descriptive analysist content (analisis deskriptif konten). Hasil penelitian yang ditemukan adalah pemikiran Habib Husein Ja’far al Hadar dalam menyampaikan tentang wasathiyyah sangat diperlukan mengingat banyaknya ancaman radikalisme, rasisme dan fanatisme terkhusus gen-Z yang mudah terprovokasi. Dalam konteks sosial, budaya, dan agama, penting bagi gen-Z untuk memahami dan menghormati keragaman yang ada, menjunjung tinggi nilai-nilai moderasi dalam beragama, dan bekerja sama dalam menciptakan lingkungan yang harmonis dan toleran. Dari penyampaian Habib Ja’far sangat mudah di terima berbagai kalangan. Adapun media yang sering ia gunakan dalam berdakwah adalah media sosial.Kata Kunci: Al-Wasathiyyah, Habib Ja’far, Gen-Z.